DEMOCRATIZATION OF THE SOCIAL ENVIRONMENT OF HIGHER EDUCATION INSTITUTION AS A PREREQUISITE FOR THE INDIVIDUALS' DEVELOPMENT POTENTIAL OF THE SUBJECTS OF ITS ACTION - Volodymyr Ryabchenko ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
There are following prerequisites outlined in this article: worldwide democratization trend; complexity of structures of social systems; growing needs in human capital development; autonomy of national higher education institutions; civilizational problem of Ukraine in national elite. Conceptual problems on a road to real democracy in higher education institutions were actualized and analyzed. Determined and characterized three models of higher education institutions activities based on the level of democratization needs of their social environment as: negative, neutral and favorable.